Sustainable forest management in northern Fennoscandia (NORFOR). Seminar on forest regeneration and management in Salla, Finland, 29- 30 September, 2009 - Hyppönen, Mikko; Tapaninen, Sirkka; Metsäntutkimuslaitos / Rovaniemi (Finnish Forest Research Institute, 2010)
Forests are extremely important for regional development and welfare in northern Fennoscandia, and the problems and questions related to forest management and forest research are very similar in all the countries in the area. Forest management in the severe northern conditions is based on scientific knowledge produced by the national forest research institutes and universities. However, there has so far been relatively little cooperation in research on forest management between the countries. Since 2007, the NORFOR network of sustainable forest management in northern Fennoscandia has initiated a number of cooperative projects and arranged meetings, workshops and excursions focused on forest management in the harsh climatic conditions of northern Fennoscandia. The main topics have been natural regeneration and direct seeding of Scots pine, damage by pathogens and pests, the interplay between forestry and reindeer husbandry, and the risk management and profitability of different silvicultural regimes. The overall aim of the NORFOR network is to establish a borderless platform in the field of research and higher education of forest management, and to create an action plan for the platform for the next few years. The objectives of the seminars, workshops and other events are, with the focus on the above topics (i) to present ongoing research in the different countries, (ii) to draw up concrete plans for cooperative research and researcher exchange between the relevant organizations, (iii) to prepare plans providing opportunities for students to carry out thesis or diploma work at universities and universities of applied science within the platform, and (iv) to perform benchmarking for sustainable forest management practices, especially forest regeneration.This issue of Metla s Working Papers is a compilation of the extended abstracts of the NORFOR seminar on forest regeneration and management held in Salla, Finland, 29 30 September, 2009. The main goal of the seminar was to discuss the main topics of NORFOR ...